Persistent Renal Dysfunction in Patients Undergoing Primary Percutaneous Coronary Intervention for Acute Myocardial Infarction. Issue 23 (3rd December 2019) - Kurogi, Kazumasa; Ishii, Masanobu; Sakamoto, Kenji; Komaki, Soichi; Marume, Kyohei; Kusaka, Hiroaki; Yamamoto, Nobuyasu; Arima, Yuichiro; Yamamoto, Eiichiro; Kaikita, Koichi; Tsujita, Kenichi
Abstract : Background: The long‐term prognosis of patients with acute myocardial infarction who develop persistent renal dysfunction (RD) remains unclear. We investigated risk factors and prognostic implications of persistent RD after contrast‐induced nephropathy (CIN) in patients with acute myocardial infarction after primary percutaneous coronary intervention. Methods and Results: We enrolled 952 consecutive patients who underwent primary percutaneous coronary intervention for acute myocardial infarction. CIN was defined as an increase in serum creatinine levels ≥0.5 mg/dL or ≥25% from baseline within 72 hours after percutaneous coronary intervention. Persistent RD was defined as residual impairment of renal function over 2 weeks, and transient RD was defined as recovery of renal function within 2 weeks, after CIN. The overall incidence of CIN was 8.8% and that of persistent CIN was 3.1%. A receiver‐operator characteristic curve showed that the optimal cutoff value of the contrast volume/baseline estimated glomerular filtration rate ratio for persistent CIN was 3.45. In multivariable logistic analysis, a contrast volume/baseline estimated glomerular filtration rate >3.45 was an independent correlate of persistent RD. At 3 years, the incidence of death was significantly higher in patients with persistent RD than in those with transient RD ( P =0.001) and in those without CIN ( P <0.001). Cox regression analysis showed that persistent RD (hazard ratio, 4.99; 95% CI, 2.30–10.8; P <0.001) was a significant risk factor for mortality. A similar trend was observed for the combined end points, which included mortality, hemodialysis, stroke, and acute myocardial infarction. Conclusions: Persistent RD, but not transient RD, is independently associated with long‐term mortality. A contrast volume/baseline estimated glomerular filtration rate >3.45 is an independent predictor of persistent RD.